Factors influencing academic dishonesty among students in Universiti Teknologi Mara Perlis / Norhasnidiana Abdul Jalil - Abdul Jalil, Norhasnidiana
This study aimed to investigate factors influencing academic dishonesty among students in Universiti Teknologi MARA (UiTM) Arau, Perlis. Variables tested in this study included self-efficacy, peer behaviour, personal beliefs and values, time pressure, procrastination and attitude. Researcher wants to know whether these independent variables will give effect on the dependent variable which is academic dishonesty and mediator which is attitude. The researcher also has prepared 367 set of questionnaires to distribute them to targeted participants who are among students in Universiti Teknologi MARA (UiTM) Arau, Perlis. The results revealed that self-efficacy, peer behaviour, time pressure and procrastination have positive significant effect on the intention to commit academic dishonesty, surprisingly only attitude and personal beliefs and values have negative effect. Researcher conducted mediation analysis between independent variables, dependent variable and a mediator. The result showed that mediator variable was not significantly predictor of academic dishonesty. However, all independent variables related with mediator effect which was attitude. The limitation of study, significance of study and recommendations for future research also discussed. Keywords: Self-efficacy, Peer behaviour, Personal beliefs and values, Time pressure, Procrastination, Attitude, Academic Dishonesty, UiTM students.